2020
DOI: 10.1111/odi.13641
|View full text |Cite
|
Sign up to set email alerts
|

Tooth extraction without discontinuation of oral antithrombotic treatment: A prospective study

Abstract: Objective: To identify which variable, among those related to surgeries, to patients, or to antithrombotic treatments, could be considered as a bleeding indicator, and to analyze effectiveness of the local hemostatic protocols used, incidence of bleeding and healing index, depending on the number of extracted teeth, and patient antithrombotic treatment.Methods: Patients who underwent tooth extractions without interruption or reduction of antithrombotic treatment were prospectively followed. The exact two-taile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Several studies have investigated the outcome of dental extraction without stopping or modifying the antithrombotic treatment. Their results revealed that, when obtaining sufficient hemostasis upon the completion of this procedure, tooth extraction could be done safely without any adjustment to the patients' antithrombotic therapy [8][9][10][11] . Consequently, this step is not justified and has become less popular.Although tooth extraction has been shown to be safe in patients with higher bleeding risk, postoperative bleeding events have still been reported 12 .…”
mentioning
confidence: 99%
“…Several studies have investigated the outcome of dental extraction without stopping or modifying the antithrombotic treatment. Their results revealed that, when obtaining sufficient hemostasis upon the completion of this procedure, tooth extraction could be done safely without any adjustment to the patients' antithrombotic therapy [8][9][10][11] . Consequently, this step is not justified and has become less popular.Although tooth extraction has been shown to be safe in patients with higher bleeding risk, postoperative bleeding events have still been reported 12 .…”
mentioning
confidence: 99%